First report of potato cyst nematode Globodera pallida (Stone, 1973) infecting potato (Solanum tuberosum L.) in Kenya - Mburu, H.; Cortada, L.; Mwangi, G.; Gitau, K.; Kiriga, A.; Kinyua, Z.; Ngundo, G.; Ronno, W.; Coyne, D.; Holgado, R.; Haukeland, Solveig (Scientific Societies, 2018)
The potato cyst nematodes (PCN) Globodera pallida (Stone, 1973) and G. rostochiensis are key pests of potato, subject to strict quarantine regulations worldwide (EPPO 2013a). Indigenous to South America, they have spread to numerous potato-growing regions around the world. G. rostochiensis was reported from Kenya in 2015 (Mwangi et al. 2015). During a nationwide survey conducted in 2016, G. pallida was detected in Kenya at an altitude of 2,349 m above sea level in Nyandarua County (0.3150195° N, 36.48328° E). Cysts were extracted from a 200 cm3 soil sample following EPPO diagnostic protocol (EPPO 2013a), and then handpicked under a stereo microscope. The PCNs recovered showed morphometric characteristics of G. pallida and are reported here. For further studies, the Nyandarua field was resampled in February 2017 to collect additional soil samples and confirm the occurrence of G. pallida. From the collected cysts, 10 cysts were inoculated on potato (Solanum tuberosum L.) ʻShangiʼ in five pots with sterile soil and sand (1:1) and grown in a screenhouse for 3 months from May to July 2017; the multiplication rate at harvest was X— = 3.6 and PCNs were recovered from potato roots and soil. Morphometric characters showed: Granek’s ratio (n = 33) ranged from 1.53 to 4.52 µm (X— = 2.78 ± 0.78 µm), and the distance from anus to vulval basin was 34.03 to 91.45 µm (X— = 52.75 ± 13.73 µm). The stylet length of the second-stage juveniles (J2s) (n = 97) ranged from 15.87 to 25.18 µm (X— = 21.87 ± 1.43), stylet knobs displayed robust tulip/anchored shape. The lengths of the hyaline tail (HT) and the true tail (TT) ranged from 15.54 to 50.44 µm (X— = 23.94 ± 4.23) and 31.02 to 79.59 µm (X— = 50.64 ± 5.71 µm), respectively. Body length (n = 40) fluctuated from 338.41 to 468.34 µm (X— = 432.23 ± 24.95). DNA amplification was performed from 14 cysts and 25 J2s using the multiplex-PCR method adapted from Bulman and Marshall (1997) and the ITS1-5.8S-ITS2 regions (Tirchi et al. 2016). PCR cycling parameters were adjusted to a 5-min initial denaturation phase and 37 PCR cycles for multiplex-PCR (EPPO 2013b). The species-specific primers ITS5/PITSp4 for G. pallida (265 bp) and AB28/TW81 primers (1,188 bp) were used to amplify the small subunit of the 18s ribosomal RNA and the ITS region, respectively; PCR-amplicons were purified using the QIAquick PCR Purification Kit (Qiagen, U.S.A.) and the DNA sequences were manually edited using BioEdit Sequence Alignment Editor; in silico analyses were conducted with the NCBI-BLAST tool. The Kenyan ITS5/PITSp4 sequences (NCBI accession no. MG309873) presented 100% similarity to the G. pallida isolates KJ409623.1 and AF016869 (score = 481; E value = 5.02e−132), while the Kenyan AB28/TW81 sequence (NCBI accession no. MG309920) showed 95 and 94% similarity to the G. pallida isolates HF583248.1 and HQ670272.1 (score = 1,218 and 1,221; E value = 0), respectively. This first report of G. pallida in sub-Saharan Africa has paramount phytosanitary and regulatory implications for potato growers and traders, national extension services, and policy makers in Kenya and the surrounding region.